Strategi Dakwah Majelis Taklim Mushola Al-Falah Haurgeulis Dalam Meningkatkan Jamaah - Siti Syarah Afifa; Ahmad Asrof Fitri; Mulkannasir Mulkannasir (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The taklim council, as a form of preaching organization and religious studies, has now been packaged with appropriate preaching strategies in order to attract young people to study religion while not appearing outdated. The taklim council Al-Falah, which is the first place in Haurgeulis for Islamic religious studies specifically for Muslim women, was established in early 2018 with only eight members and now has around 100 members. The increase in congregations in less than two years demonstrates that the taklim council’s preaching strategy has been quite successful. This paper provides an understanding how preaching strategies uses by the taklim council Al-Falah Haurgeulis of increase in the congregation. This study uses a qualitative field research method with descriptive analysis. In-depth interviews, observation, and documentation were used to collect data. According to the findings of this study (1) formulating a preaching strategy by examining the relationship between the organization and its environment, (2) the use of preaching strategies in the field implementation process are sentimental strategies, rational strategies, and sensory strategies, (3) Do evaluations and show changes in the congregation is viewed in terms of quantity and quality.